Colonoscopy: A study of findings in 332 patients (Journal of Chittagong Medical College Teachers' Association, 2009)
Key words: colonoscopy; abdominal pain; lower GI bleeding; mass lesion; therapeutic yielddoi: 10.3329/jcmcta.v18i2.3833Journal of Chittagong Medical College Teachers' Association 2007: 18(2):28-31